Peran Kiai Dalam Pendidikan Moderasi beragama Pada Keluarga Beda Agama di Dusun Malatan Desa Bansari Kecamatan Bansari - Setyawati, Yulia; Nasihin, Husna; Faizah (Jurnal Studi Pesantren, 2024)
The problem of religious moderation is an issue between religions and its implementation in society which causes negative impacts that need to be taken into account. One of the most serious impacts of religious immoderation is the emergence of religious extremism. Apart from extremism, radical groups also often use religion as a justification for acts of violence and terrorism. The problems of religious moderation also include systemic discrimination that leads to societal inequality in receiving various aspects of life, including education, employment and political participation.The purpose of this research is to determine the role of Kiai in religious moderation education in interfaith families. This study used qualitative research methods. This research investigates and analyzes religious moderation education activities in families of different religions and the role of Kiai in families of different religions. The research results show; religious moderation education activities in interfaith families, the role of Kiai in religious moderation education in interfaith families. Forms of activities such as; hosting yasinan, gathering activities during Eid al-Fitr celebrations, family meetings, attending village sadranan events, and serving food during the tadarus of the fasting month. Meanwhile, the Kiai's role is to provide understanding to families of different religions and to be role models. The implication is that being able to shape personality in a social environment through the application of religious moderation is able to increase people's insight into the role of Kiai in religious moderation education. Thus, it is very important for this research project to be carried out in more depth.